The impact of protective grounding deviation on the surge protection device - H’ng, Song Tian (2022)
A power surge, such as lightning, destroys electrical and electronic components and threatens human life. Surge protection devices (SPD) are installed as a protective measure to prevent power surge events. However, the SPD requires good protective grounding to function well. Without adequate grounding, SPD may not be able to protect the system and the connected loads. This project investigates the effects of different earthing layouts, different grounding resistances, and the impact of harmonic distortion on SPD performance. The SPDs applied in this project are the conventional type (MOV) and the power device type (MOSFET). A surge generator that complies with the IEC 61000- 4-5 standard is created and applied to these earthing layouts via MATLAB Simulink software. The SPD performance is not affected by the type of earthing layouts. The increase in grounding resistance value improves the clamping effect for the MOV but reduces for the MOSFET. Besides, when harmonic distortion is added, the protection efficiency for both SPDs is affected. Harmonic distortion affects the SPD performance by distorting the voltage supplied. The MOSFET has a better response time and fall time at lower grounding resistance than the MOV. However, when the grounding resistance increases, the MOV response time and fall time are faster. This shows that the MOSFET is suitable for earthing systems with low grounding resistance. In comparison, the MOV is suitable for the earthing system with high grounding resistance.